Corrosion of superheater materials by alkali chloride salt mixtures – The role of the presence of molten phase. (15th July 2023) - Hupa, Elisa; Vainio, Emil; Yrjas, Patrik; Engblom, Markus; Hupa, Mikko
Highlights: The role of increasing amount of molten phase on corrosion of stainless steel was studied. A certain critical percentage of molten phase was required before observing severe corrosion. This is believed to be caused by the increased steel/salt-melt contact. The critical amount of molten phase at T0 for severe corrosion is steel specific. Abstract: In biomass combustion, the presence of alkali chlorides will lower the ash deposit melting temperature. It is also known that aggressive corrosion of superheater materials may occur in the presence of melt in contact with the steel. Therefore, the first melting temperature (T0 ) has been used as a guideline for the maximum superheater temperature. However, the impact of the share – or percentage - of molten phase in the salt deposit on corrosion has not been systematically investigated. In this work, the role of the share of molten phase on the corrosion of two stainless steel qualities, AISI 347 and 310, was studied. The salt mixtures used (NaCl-Na2 SO4 and KCl-K2 CO3 ) were prepared to produce different amounts of melt at the higher test temperature. The steels were exposed for one week to a salt mixture in a tube furnace, at temperatures both below and above T0 . After the exposure, the samples were cut to reveal the cross-sections. The cross-sections were analysed by means of SEM-EDX. Remarkable differences in the corrosion tendencies of the materials were observed depending on the percentage of molten phase. The work revealed that for a certain steel quality a given minimum percentage of molten phase was required before observing severe corrosion. For the NaCl-Na2 SO4 salt mixtures, around 3 wt% molten phase was sufficient to significantly accelerate the corrosion rate for AISI 347, while the corresponding value was 14 wt% for AISI 310. The criterion of first melting temperature T0 being the critical limit for severe superheater corrosion requires modification. The amount of liquid phase at T0 is also essential. The critical amount of liquid phase at T0 for severe corrosion is steel specific.